Case Study of the Potential of Indonesian Series C Technology Startup Companies Aplikasi Supers in Becoming a Profitable Company while Maintaining Growth Company Operational Performance - Matthew Adrian Tirtamarta; Nugroho Purwanto (Jurnal Pendidikan Indonesia, 2024)
This research aims to find out how the company's growth and the ability of the Aplikasi Super company to survive without funding from investors can be fulfilled and produce value and useful solutions for the Aplikasi Super in the future. The analysis was carried out using the case study method which emphasizes one case on the Aplikasi Super which will be reviewed in this study. The results of this study indicate that the Aplikasi Super currently applies an equity investment and stock dilution funding system. The aim of the Aplikasi Super to develop as an independent company is realized by planning new strategies and concepts so as to create potential that can be developed so that it becomes a positive impact, especially for Aplikasi Super funding. From 2021-2022 the Aplikasi Super is not in a profitable condition, with an ROA of -1.15, this means that the company's net profit is lower than zero or that the company's losses exceed the total value of its assets, but this assessment cannot be concluded absolutely from one just a factor, looking at it from a Aplikasi Super perspective that must maintain growth and profitability while making conditions more difficult to control so this can happen. The concept or strategy developed by Aplikasi Supers in this case can be seen from the company evaluating the gross margin, namely the difference between revenue and production costs, as the main indicator of company profits. Super Apps also takes steps to improve operational efficiency by using technology